Deduction Difficulties. Issue 1 (23rd February 2018) - Howell, Robert
Abstract: I argue, contrary to Dennis Schulting in Kant's Radical Subjectivism, that the main reasoning of Kant's transcendental deduction of the categories is progressive, not regressive. Schulting is right, however, to emphasize that the deduction takes the object cognized to be constituted in an idealism-entailing way. But his reasoning has gaps and bypasses Kant's most explicit deduction argument, independent of the Transcendental Aesthetic, for idealism. Finally, Schulting's claim that Kantian discursivity itself requires idealism overlooks the fact that Kantian general judgements can be true in a domain of objects without being specifically of or about any particular ones of those objects.